2016
DOI: 10.1016/j.micpath.2015.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism and oxidative profile of dogs naturally infected by Ehrlichia canis : Acute and subclinical disease

Abstract: The aim of this study was to evaluate the oxidant profile and iron metabolism in serum of dogs infected by Ehrlichia canis. Banked sera samples of dogs were divided into two groups: negative control (n = 17) and infected by E. canis on acute (n = 24), and subclinical (n = 18) phases of the disease. The eritrogram, leucogram, and platelet counts were evaluate as well as iron, ferritin, and transferrin levels, latent iron binding capacity (LIBC), and transferrin saturation index (TSI) concentration. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…As antioxidant biomarkers, three assays commonly used to evaluate the total antioxidant capacity (TAC) were included in this study: trolox equivalent antioxidant capacity (TEAC), cupric reducing antioxidant capacity (CUPRAC), and ferric reducing ability of plasma (FRAP), as well as two individual antioxidants, uric acid and thiol [20][21][22]. Regarding oxidant status, it was evaluated using assays for ferrous oxidation-xylenol orange (FOX) levels, total oxidant content (TOS), advanced oxidation protein products (AOPP) and hydrogen peroxide (H 2 O 2 ) [23].…”
Section: Introductionmentioning
confidence: 99%
“…As antioxidant biomarkers, three assays commonly used to evaluate the total antioxidant capacity (TAC) were included in this study: trolox equivalent antioxidant capacity (TEAC), cupric reducing antioxidant capacity (CUPRAC), and ferric reducing ability of plasma (FRAP), as well as two individual antioxidants, uric acid and thiol [20][21][22]. Regarding oxidant status, it was evaluated using assays for ferrous oxidation-xylenol orange (FOX) levels, total oxidant content (TOS), advanced oxidation protein products (AOPP) and hydrogen peroxide (H 2 O 2 ) [23].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia, anemia and lymphopenia were also related to the action of Ehrlichia in the bone marrow and lymphoid tissues (Mylonakis et al 2004, Greene 2006. Recent studies about iron metabolism in animals infected with Ehrlichia canis, reported a marked decreased in circulating iron, suggesting that the host may be induced by the bacteria to transport iron to infected tissue for bacterial multiplication, contributing to anemia (Bottari et al 2016). This may explain the numerous hemosiderin granules commonly found in the bone marrow, liver, lymph nodes and spleen from animals with ehrlichiosis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of lipid peroxidation and decreased activities of superoxide dismutase, glutathione, and catalase have been shown in natural co-infections with CME, babesiosis, anaplamosis, and hepatozoonosis (36). Bottari et al (2) found higher levels of advanced oxidation protein products and the ferric-reducing ability of plasma in acute and subclinical phases of CME. The present study aims to represent the oxidative status with total and individual parameters and to show their relationship to the lipid profile.…”
Section: Co-infected (N = 23)mentioning
confidence: 98%
“…Oxidative stress and increased lipid peroxidation has been shown in dogs with CME because of free-radical activity and an impaired antioxidant system (2,8,36). Paraoxonase (PON-1) and arylesterase (ARE) are esterase enzymes with antioxidant properties in a complementary structure.…”
Section: Praca Oryginalnamentioning
confidence: 99%